The Influence Of Discipline On Professionalism Of Health Personnel At Aura Shifa Hospital Kediri - Ria Anka Sari; Agustin Widyowati; Amarin Yudhana; Wening Palupi Dewi (Journal of Hospital Management and Services, 2023)
Professionalism of health workers is an important concept in achieving status as a profession, however professionalism is only taught as a theory and concept so it looks abstract and difficult to apply to clinical practice. Success in developing a professional identity as a continuous transition process from education to becoming a professional health worker is influenced by many factors, one of which is discipline. The aim of this research is to analyze the influence of discipline on the professionalism of health workers at Aura Shifa Hospital Kediri. The design of this research is quantitative observational research with a cross sectional approach carried out at Aura Shifa Hospital Kediri. The total population was 197 respondents and the sample was 132 respondents taken using the Stratified Random Sampling technique. The findings showed that the majority of respondents had sufficient discipline, 74 respondents (56.1%). Almost all respondents had sufficient professionalism category, 101 respondents (76.5%). Based on the results of the Linear Regression analysis, it shows that the p-value is 0.000 < 0.05, so H1 is accepted so it is concluded which means that partially there is an influence of discipline on the professionalism of health workers at Aura Shifa Hospital Kediri with an influence size of 54.3%. Therefore, instilling an attitude of discipline and professionalism at Aura Syifa Hospital can continue to be a trusted place for health services and make a positive contribution to patients.